Computational screening of trace elemental concentrations in Hemidesmus indicus L. A potential herbal plant used against skin diseases by ED-XRF-Technique. (2021) - Jyothsna, S.; Manjula, G.; Chandar Rao, P.; Mahesh Kumar, A.; Sammaiah, D.; Nageswara Rao, A.S.
Abstract: The present investigation reports on the screening of 13 trace elemental concentrations in the leaves of Hemidesmus indicus, an anti-skin disease medicinal plant of Telangana by ED-XRF technique. ED-XRF spectrometer is a non destructive, multi-elemental capability, excellent sensitivity and low detection limits for large atomic numbers. The elements like P, Cl, S, K, Mn, Ca, Cu, Fe, Se, Br, Zn, Sr, and Rb were identified and its concentration determined. From the present results the concentration of Cl, Ca, Mn, Fe, Cu, Zn Se, Rb, Sr and Br were found at a higher level while the concentration of P, S and K identified at minor level compared with NIST 1515 apple leaf. Present data indicate that, the safe use of this herbal plant leaves in the conventional treatment of skin disorders because this medicinal plant leaves are contain substantial quantity of Mn, Fe, Cu, Zn, and Se.